Serum Ferritin as a Prognostic Biomarker for Severe Dengue Infection: A Systematic Review and Meta-Analysis - Putu Ari Paramitha Widiani; Si Ngurah Oka Putrawan; I Nyoman Windiana (Phlox Institute: Indonesian Medical Research Organization, 2026)
Introduction: Severe dengue drives mortality and poses critical triage challenges in adult internal medicine. Because standard WHO warning signs often manifest late in the disease course, early and inexpensive laboratory markers for risk stratification are urgently needed. Methods: Following PRISMA 2020 guidelines, we conducted a systematic review and random-effects meta-analysis of adult observational studies comparing serum ferritin between severe and non-severe dengue. Standardised mean differences were pooled as Hedges' g utilizing the DerSimonian-Laird estimator with Hartung-Knapp-Sidik-Jonkman correction. Heterogeneity was quantified using Cochran's Q, I², τ², and 95% prediction intervals. Results: Twelve studies (n=1,479) were qualitatively synthesized; five adult cohorts (n=495) provided continuous data for quantitative meta-analysis. Serum ferritin was significantly elevated in severe dengue, yielding a large pooled effect size (Hedges' g = 1.022; 95% CI 0.494–1.551; p=0.006). Despite substantial between-study heterogeneity (I²=78.1%; 95% PI -0.12 to 2.17), the effect direction remained consistently positive across geographic subgroups (Asia, Latin America) and demonstrated robust stability in leave-one-out sensitivity analyses. Conclusion: Adults with severe dengue demonstrate substantially higher serum ferritin levels than those with non-severe disease. Characterized by a robust effect size across diverse regions, serum ferritin serves as a promising, widely accessible adjunct to existing WHO warning signs, optimizing early risk stratification and clinical triage in resource-constrained tropical settings.